Renewable energy development and climate change mitigation in Malaysia: a legal study - Ghazali, Farahdilah; Ansari, Abdul Haseeb; Mustafa, Maizatun; Wan Zahari, Wan Mohd Zulhafiz (Universiti Malaysia Terengganu, 2019)
The devastating impacts of climate change have driven the development of renewable energy (RE), and it is seen as a game changer to preserve the environment for generations to come. The commitment under the Paris Agreement to the United Nations Framework Convention on Climate Change has indirectly forced many countries to support the efforts for RE generation. This energy transition from unsustainable fossil fuels to RE was demonstrated by the promulgation of various laws and policies at national, regional and international levels. Aligned with that, Malaysia has also taken several measures in mitigating climate change impacts and accelerating RE development. Thus, this study focuses on the importance of RE generation as part of the climate mitigation regime with reference to the Renewable Energy Act 2011 (Act 725). This study adopts a black-letter approach through statute analysis. Throughout this paper, it was suggested that the Renewable Energy Act 2011 failed to address climate change issues properly. Therefore, this paper calls for a reform to incorporate climate change mitigation and sustainable development in the existing law.